EP870 Bevacizumab facilitates surgery in previously inoperable patients with low-grade serous ovarian cancer: a case series. (1st November 2019) - Hockings, H; Wood, G; Lockley, M
Abstract : Introduction/Background: Low grade serous ovarian cancer (LGSOC) accounts for 10% of serous epithelial ovarian cancers. In contrast to high grade serous ovarian cancer (HGSOC), it is characterised by an early age of onset, indolent growth rate and relative resistance to chemotherapy. The use of bevacizumab in ovarian cancer has mostly been investigated in HGSOC and is contra-indicated in patients with extensive disease associated with the bowel, due to risks of bowel perforation. Several single-institution studies have reported activity of bevacizumab in LGSOC in the recurrent disease or adjuvant setting. We present two patients with advanced LGSOC and extensive serosal disease involving the bowel that were treated with bevacizumab prior to surgery in the first-line setting. Methodology: Case notes, pathology results and CT scans were reviewed. Histology slides from initial biopsy and debulking surgery specimens were stained for H&E to assess chemotherapy-response scores. Results: Both patients had Stage IIIC disease, with extensive disease involving the bowel which prohibited surgery. No response was seen on CT scan or serum Ca125 levels after three cycles of carboplatin and paclitaxel, but following the addition of bevacizumab both patients had a marked reduction in disease volume. Serum Ca125 levels reduced to near-normal values following these three cycles of combined carboplatin, paclitaxel and bevacizumab (438 to 50 and 151 to 54). In both cases surgical debulking with complete macroscopic resection was achieved. There were no adverse events associated with bevacizumab use (18 cycles 7.5 mg/kg). Conclusion: We propose that Bevacizumab may be safe in LGSOC patients with extensive bowel involvement, and can facilitate surgery in those patients that were previously inoperable. Further evaluation of its use in the first-line treatment of LGSOC is warranted as options for neo-adjuvant therapy are severely limited. We have commenced an observational study including all stage III/IV LGSOC patients receiving neo-adjuvant Bevacizumab. Disclosure: Nothing to disclose.